Evidence for two-component superconductivity in the femtosecond optical and transient photoconducting response of YBa2Cu3O7-delta. - Mihailovic, D; Stevens, C; Podobnik, B; Demsar, J; Zavrtanik, M; Smith, D; Ryan, J (1997)
Femtosecond time-resolved spectroscopy and transient photoconductivity measurements have been used to investigate the time-dynamics, frequency dependence and symmetry of electronic excitations associated with the opening of the superconducting gap in YBa2Cu3O7-delta. Two clearly identifyable relaxation components are observed operative on nanosecond and picosecond timescales respectively, implying the co-existence of localized states and band-like carriers both in the superconducting and normal state. From the temperature dependence of the two components it is clear that both relaxation phenomena are directly connected with the formation of the superconducting condensate. The spectral response for both excitations closely follows the spectrum observed in thermal modulation spectroscopy and implies that the electron-boson coupling function includes a charge-transfer component at optical excitation energies in the region of 1.5-2 eV.